Request strategies in Burmese - Rattanapitak, Ampika (2024)
This study investigates request strategies in the Burmese language. The main data come from a questionnaire and are supplemented by observations. Burmese requests were analyzed based on the model of Blum-Kulka, House and Kasper (1989). The results show that there are three main request strategies in Burmese: direct, conventional indirect, and non-conventional indirect. In terms of the preference strategy, both direct and conventional indirect requests are preferred in Burmese. This does not support the universal request phenomena proposed by Blum-Kulka et al. Although direct requests may be considered impolite in other languages, this is not necessarily the case in Burmese, because Burmese people modify their request by using internal modifications.